The role of packaging in omni-channel fashion retail supply chains: How can packaging contribute to logistics efficiency? - Stephan L. K. Freichel; Johannes Wollenburg; Johannes K. Wörtge (Logistics Research, 2019)
Omni-channel retailing changes the distribution structures of retail companies. Integrating existing facilities, resources and processes may hold advantages regarding customer satisfaction and shopping convenience, as well as logistical efficiency, but are complex in the implementation. Since the logistical requirements for the packaging system in stationary and distance channels are different due to varying shipment structures, this hinders seamless channel integration. This paper investigates the role of the packaging system in omni-channel fashion distribution and identifies the respective challenges retailers and associated supply chain partners face regarding packaging when integrating sales and logistics channels. By means of a qualitative research approach including nine interviews from field experts, the current practices of retailers, packaging manufacturers and logistics service providers regarding packaging in Omni- Channel retail are derived. The results indicate that the requirements towards packaging in the different channels, especially in integrated DC structures, interfere with a seamless channel integration. With regard to the role of stores in omni-channel retailing, channel-adequate packaging types need to be used for store pick-ups, and related process-changes are necessary for eightening efficiency. Packaging represents a restriction for distance shipments, fulfilled by stores. Primary packaging is an opportunity to support channel integration. However, this requires early and cross-company collaboration. The main theoretical contribution of this paper lies in identifying packaging related challenges preventing seamless channel integration into omni-channel distribution, stating initial packaging solutions to overcome those and providing an outlook towards future requirements for packaging in an omni-channel world. The paper has also strong managerial implications for retailing companies implementing integrated omni-channel structures, processes and services.
Keywords: 650; omni-channel retail; distribution; packaging; fulfilment; retail logistics